PENJAJAHAN BARAT ATAS DUNIA ISLAM DAN PERJUANGAN KEMERDEKAAN NEGARA NEGARA ISLAM - Ika Kholpiana Sari Marbun; Muhammad Basri; Khofifa Juliana Pilpers (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The colonization of the Islamic world by Western countries in the 19th and early 20th centuries had a major impact on economic, political and social aspects. European countries such as England, France, and the Netherlands conquered much of the Islamic world, leading to the exploitation of natural resources and major changes in social and political structures. This colonial process gave rise to resistance and struggles for independence in various Islamic countries. The method used to collect data in this research was literature study. Library research is research conducted based on information from scientific publications, previous research or other written sources that support the discussion in this writing. This research concluded that the unity of Muslims is the key to achieving independence, with an awareness of the value of -shared values ​​form the basis of the struggle movement. Resistance and liberation movements emerged in response to colonialism, with nationalist leaders leading armed struggle and diplomacy to achieve independence. This struggle reflects the desire to restore traditional identities and values ​​marginalized by Western domination.